The Problem of Comparative-Historical Nature of the Soviet Bureaucracy in Theoretical Heritage of L.D. Trotsky - V. P. Makarenko; Reefat Kamaleldin Badawy Khaled (Сравнительная политика)
The article identifies and analyzes the essential provisions of Trotsky's concept regarding the Soviet bureaucracy. Its nature is determined by the connection with the genesis of Stalin's regime of personal power. The intellectual and philosophical tendencies of bureaucracy are a complex of procedures of thought and action, on which the regime of personal power is based as a modification of the enlightened monarchy, the Orthodox Church and the police state. Theories arising in these religious-political forms justify bureaucratic thinking. The history of European and Russian social thought can be studied as a process of selecting those theories that refute bureaucratic thought and practice and counteract the concentration of power in one hand. A historiographic concept is needed for which the value of the state and bureaucracy is not the main one.According to the paper, Trotsky's views on the Soviet bureaucracy form an important link in the theory and practice of political resistance to the regime of personal power. The history of the USSR is the history of the struggle of the Soviet bureaucracy for its share in revenues and in power. The Stalinist ways of understanding the theory of Marx and the practice of Lenin are false and lead to the bureaucratization of the party and state. There is a similarity between the political practice of Stalin, the activities of the Orthodox Church, the police state, Italian fascism and German Nazism. Any theoretical works commissioned by the pinnacle of the bureaucracy contain the danger of reproducing all the features of the Stalinist way of thinking and acting.